Carbon cloth-based three-dimensional current collector material and preparation method, lithium metal negative electrode, battery
Patent Information
- Application Number
- CN202611233512.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的主要目的在于提供一种碳布基三维集流体材料及制备方法、锂金属负极、电池,旨在解决现有的锂负极制备和应用性能较差的问题
[0015]本发明提供一种碳布基三维集流体材料的制备方法,将常规碳布预处理步骤升级为“清洗+化学改性”一体化工艺,一步操作同时实现杂质去除和表面官能团引入,工艺简洁高效;通过“先净化后改性”的顺序设计,净化步骤为后续酸处理提供了清洁的反应界面,确保了酸处理中化学键合反应的均匀性和可重复性;经上述方法处理后的碳布表面由原本的疏锂(亲锂性差)状态转变为亲锂状态;酸处理的时间窗口既保证了改性效果,又避免了对碳纤维结构的过度损伤,处理后碳布的拉伸强度更好。酸处理后的碳布展现出对锂金属更低的成核过电位,由酸处理的碳布制备的锂金属负极组装的对称电池展现出更好的电化学性能,拥有更小的电压分布。
Smart Images

Figure CN122992083A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium metal anode technology, and in particular to a carbon cloth-based three-dimensional current collector material and its preparation method, a lithium metal anode, and a battery. Background Technology
[0002] Lithium metal is known for its extremely high specific capacity (3860 mAh g). -1 With its low electrochemical potential, lithium metal is widely considered the most promising anode material for next-generation rechargeable batteries. However, lithium metal still faces challenges during cycling, including high chemical activity, significant volume expansion, an unstable solid-state electrolyte interface (SEI), and disordered dendrite growth. These challenges result in low coulombic efficiency, short cycle life, and even safety hazards in high-energy-density batteries that directly use lithium metal anodes, severely hindering their practical application.
[0003] To address these bottlenecks, researchers have proposed various strategies, including optimizing electrolyte formulations, employing solid-state electrolytes, constructing artificial SEI films, and designing three-dimensional structured anodes. Among these, constructing lithium metal hosts based on carbon materials has attracted significant attention due to its abundant sources, tunable structure, good conductivity, and high mechanical stability, and is considered a promising approach to alleviating lithium anode problems. However, common carbon materials such as carbon cloth and carbon fibers have inherently poor lithium wettability, leading to high nucleation overpotentials, uneven deposition, and difficulty in effectively suppressing dendrites. In summary, existing lithium anodes exhibit poor performance in both preparation and application. Summary of the Invention
[0004] The main objective of this invention is to provide a carbon cloth-based three-dimensional current collector material and its preparation method, a lithium metal anode, and a battery, aiming to solve the problem of poor performance in the preparation and application of existing lithium anodes.
[0005] To achieve the above objectives, the present invention provides a method for preparing a carbon cloth-based three-dimensional current collector, comprising the following steps: Commercial carbon arrays were ultrasonically cleaned in a mixture of alcohol solvent and water to obtain a purified material. The purification material is immersed in an acid solution to introduce oxygen-containing functional groups and / or chlorine-containing functional groups on the surface of the carbon cloth, thereby obtaining a carbon cloth-based three-dimensional current collector material. The ultrasonic cleaning frequency is 20-60kHz, the immersion treatment is carried out at a temperature of 25-80℃, and the treatment time is 3-8 hours.
[0006] In one embodiment, the alcohol solvent is anhydrous ethanol, the water is deionized water, and the ultrasonic cleaning time is 0.5-2 h.
[0007] In one embodiment, the volume ratio of the alcohol solvent to the water in the mixture is 1:1.
[0008] In one embodiment, the concentration of the acid solution is 5-10 mol / L. -1 The soaking time is 2-10 hours.
[0009] In one embodiment, the acid solution is nitric acid, sulfuric acid, or a mixture of nitric acid and sulfuric acid.
[0010] The present invention also provides a carbon cloth-based three-dimensional current collector material, which is prepared by the method described in any one of the above-mentioned methods, wherein the surface of the carbon cloth-based three-dimensional current collector material contains oxygen-containing functional groups and / or chlorine-containing functional groups introduced by the acid treatment.
[0011] The present invention also provides a lithium metal anode, comprising: The carbon cloth-based three-dimensional current collector material is based on the above-mentioned carbon cloth-based three-dimensional current collector material; Lithium metal is loaded onto the carbon cloth-based three-dimensional current collector material via electrochemical deposition.
[0012] In one embodiment, the lithium metal electrodeposition capacity is 1~5 mAh cm⁻¹. -2 .
[0013] The present invention also provides a battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is a lithium metal negative electrode as described in any one of the above.
[0014] In one embodiment, the diaphragm is a glass fiber diaphragm, and the electrolyte is a diethylene glycol dimethyl ether solution containing LiPF6.
[0015] This invention provides a method for preparing a carbon cloth-based three-dimensional current collector material. The conventional carbon cloth pretreatment steps are upgraded to an integrated "cleaning + chemical modification" process, achieving impurity removal and surface functional group introduction in a single operation, resulting in a simple and efficient process. Through a "clean-then-modify" sequential design, the purification step provides a clean reaction interface for subsequent acid treatment, ensuring the uniformity and repeatability of the chemical bonding reaction during acid treatment. The carbon cloth surface treated by this method changes from its original lithium-phobic (poor lithium affinity) state to a lithium-affinity state. The time window for acid treatment ensures the modification effect while avoiding excessive damage to the carbon fiber structure, resulting in better tensile strength of the treated carbon cloth. The acid-treated carbon cloth exhibits a lower nucleation overpotential for lithium metal, and symmetric batteries assembled with lithium metal anodes prepared from acid-treated carbon cloth exhibit better electrochemical performance and a smaller voltage distribution. Attached Figure Description
[0016] Figure 1This is a flowchart of the preparation method of the carbon cloth-based three-dimensional current collector provided in the embodiments of the present invention; Figure 2 This is a schematic diagram showing that the surface of the carbon cloth after acid treatment contains functional groups such as OH, C=O, and COOH. Figure 3 This invention relates to the rate performance of a lithium metal symmetric battery assembled using an acid-treated carbon cloth three-dimensional current collector.
[0017] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indicators will also change accordingly.
[0020] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0021] Please see Figure 1 This invention provides a method for preparing a carbon cloth-based three-dimensional current collector, comprising the following steps: S10. Commercial carbon arrays are ultrasonically cleaned in a mixture of alcohol solvent and water to obtain a purified material. During the production and storage of commercial carbon fiber cloth, organic pollutants (such as spinning oils, packaging material residues, etc.) and particulate impurities inevitably adsorb onto the fiber surface. These physical adsorbates cover the active sites on the carbon fiber surface, hindering the effective contact between chemical reagents and the carbon surface during subsequent acid treatment. This invention uses an alcohol-water mixture as the cleaning medium, utilizing the solubility of alcohols in organic solvents for organic pollutants and the solubility of water in inorganic salt impurities to achieve broad-spectrum cleaning. On this basis, ultrasonic oscillation at 20-60 kHz is applied. The microjets and shock waves generated by the ultrasonic cavitation effect can physically peel off submicron-sized particles attached to the fiber surface. Ultrasonic oscillation enhances the penetration and flow of the cleaning solution within the three-dimensional woven structure of the carbon fiber cloth, ensuring that pollutants between the internal fiber bundles are also effectively removed. The selection of the ultrasonic frequency is optimized and limited: when the frequency is below 20 kHz, the cavitation bubble size is large and the cavitation intensity is insufficient; when the frequency is above 60 kHz, the cavitation effect weakens and the cleaning efficiency decreases.
[0022] S20. The purification material is immersed in an acid solution to introduce oxygen-containing functional groups and / or chlorine-containing functional groups on the surface of the carbon cloth, thereby obtaining a carbon cloth-based three-dimensional current collector material. Unlike the physical cleaning purpose of using concentrated hydrochloric acid for short-term cleaning to "remove surface oxide layer and impurities" in existing technologies, the present invention uses dilute acid for long-term treatment under heating conditions. Its technical essence is surface chemical modification rather than surface cleaning.
[0023] The ultrasonic cleaning frequency is 20-60kHz, the immersion treatment is carried out at a temperature of 25-80℃, and the treatment time is 3-8 hours.
[0024] Specifically, under heating conditions of 25-80℃, the active species (H+) in the acid solution... + Cl - (and related active chlorine species) undergo the following chemical reactions with carbon atoms on the carbon fiber surface: (1) Oxidation reaction: Under heating conditions, active oxygen species in acid solution can react with carbon atoms on the carbon fiber surface. 2 Hybrid carbon atoms undergo mild oxidation to form oxygen-containing functional groups (such as C—OH, C=O, —COOH). The electronegative oxygen atoms in these oxygen-containing groups can act as Lewis base sites and form coordination-adsorption with lithium ions (Lewis acids). (2) Chlorination reaction: When hydrochloric acid is used as the treatment acid, chloride ions can undergo electrophilic substitution with unsaturated carbon sites on the carbon fiber surface under heating conditions to form C—Cl covalent bonds and introduce chlorine-containing functional groups. (3) Mild etching: Appropriate acid concentration and temperature produce controllable micro-etching on the carbon fiber surface, increasing surface roughness and defect site density. These edge sites themselves have high lithium ion adsorption energy.
[0025] Furthermore, limiting the processing time to 3-8 hours is crucial for achieving "modification" rather than "cleaning": less than 3 hours results in insufficient chemical reaction and inadequate functional group introduction; more than 8 hours may damage the carbon fiber structure due to over-reaction, affecting the mechanical strength and conductivity of the current collector; a temperature range of 25-80℃ ensures that the chemical activity of the acid solution remains controllable, suitable for scenarios requiring precise control of the functional group introduction; heating to 40-80℃ accelerates reaction kinetics, shortens processing time, and increases functional group grafting density. An upper temperature limit of 80℃ prevents excessive volatilization of the acid solution (especially hydrochloric acid) and excessive etching of the carbon fiber.
[0026] In the preparation method of carbon cloth-based three-dimensional current collector provided by this invention, the conventional carbon cloth pretreatment step is upgraded to an integrated process of "cleaning + chemical modification". This one-step operation simultaneously removes impurities and introduces surface functional groups, resulting in a simple and efficient process. Through the sequential design of "purification before modification", the purification step provides a clean reaction interface for subsequent acid treatment, ensuring the uniformity and repeatability of the chemical bonding reaction during acid treatment. The carbon cloth surface treated by the above method changes from its original lithium-phobic (poor lithium affinity) state to a lithium-affinity state. The acid treatment time window (3-8 hours) ensures the modification effect while avoiding excessive damage to the carbon fiber structure, resulting in better tensile strength of the treated carbon cloth. The acid-treated carbon cloth exhibits a lower nucleation overpotential for lithium metal, and the symmetrical battery assembled with a lithium metal anode prepared from the acid-treated carbon cloth exhibits better electrochemical performance and a smaller voltage distribution.
[0027] Furthermore, the alcohol solvent is anhydrous ethanol, the water is deionized water, and the ultrasonic cleaning time is 0.5-2 hours. Anhydrous ethanol has moderate polarity and good volatility, and its ability to dissolve common contaminants on carbon cloth surfaces, such as organic oils and ester compounds, is superior to methanol (less toxic) and isopropanol (slightly less volatile), making it the optimal alcohol for cleaning. Deionized water avoids introducing additional metal ion impurities; the 0.5-2 hour cleaning time balances cleaning efficiency and energy consumption.
[0028] On the other hand, the concentration of the acid solution is 5-10 mol / L. -1 The soaking time is 2-10 h. A hydrochloric acid concentration of 5-10 mol / L, under heating conditions, can release active chlorine species at a moderate rate, achieving controllable introduction of chlorine-containing functional groups onto the carbon fiber surface. This results in a gentler surface etching of the carbon fiber, more complete preservation of the graphitized structure, and good conductivity. Combined with heating and long-term conditions, this achieves an optimal balance between the amount of functional group introduction and the retention of the carbon fiber structure.
[0029] In this embodiment, the volume ratio of alcohol solvent to water in the mixture is 1:1. This provides the highest overall removal rate of organic and inorganic contaminants on the carbon cloth surface. The surface tension of the mixture at this ratio is significantly lower than that of pure water, which facilitates rapid wetting and penetration of the cleaning solution into the gaps between the fiber bundles inside the carbon cloth, achieving deep cleaning. Furthermore, combined with the ultrasonic cleaning frequency (20-60kHz), it ensures uniform purification of the inner and outer surfaces of the carbon cloth.
[0030] Specifically, the acid solution is nitric acid, sulfuric acid, or a mixture of nitric acid and sulfuric acid. Nitric acid and / or sulfuric acid are suitable for embodiments that introduce oxygen-containing functional groups, while hydrochloric acid is suitable for embodiments that introduce chlorine-containing functional groups.
[0031] Please see Figure 2 Based on the above-mentioned method for preparing carbon cloth-based three-dimensional current collectors, this invention provides a carbon cloth-based three-dimensional current collector, which is prepared by the same method. That is, it has all the technical features of the carbon cloth-based three-dimensional current collector prepared by the above-mentioned method, and therefore also has the technical effects brought about by all the above-mentioned technical features, which will not be elaborated here.
[0032] The present invention provides a carbon cloth-based three-dimensional current collector material, wherein the surface of the carbon cloth-based three-dimensional current collector material contains oxygen-containing functional groups and / or chlorine-containing functional groups introduced by the acid treatment.
[0033] Furthermore, based on the aforementioned carbon cloth-based three-dimensional current collector, the present invention also provides a lithium metal anode, comprising a carbon cloth-based three-dimensional current collector and lithium metal; the carbon cloth-based three-dimensional current collector is the aforementioned carbon cloth-based three-dimensional current collector; the lithium metal is loaded onto the carbon cloth-based three-dimensional current collector by electrochemical deposition.
[0034] Furthermore, the electrodeposition capacity of lithium metal was limited to 1~5 mAh cm⁻¹. -2 This capacity range covers a wide range of applications, from thin-layer to thick-layer deposition.
[0035] The lithium metal anode using the current collector of this invention exhibits a significantly higher nucleation overpotential than the comparative anode using unmodified carbon cloth; this lithium metal anode can cycle stably with a slow increase in polarization overpotential; the porous structure in the three-dimensional carbon cloth framework effectively accommodates volume changes during lithium deposition / desorption; 1~5 mAh cm⁻¹ -2 Its deposition capacity covers a variety of application needs from consumer electronics to power batteries, and has good industrial adaptability.
[0036] Based on the above-mentioned lithium metal anode, the present invention also provides a battery including the above-mentioned lithium metal anode, and therefore also has all the technical features of the above-mentioned lithium metal anode, that is, it has all the technical effects brought about by the above-mentioned technical features, which will not be described in detail here.
[0037] The battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is a lithium metal negative electrode as described in any one of the above.
[0038] The diaphragm is a glass fiber diaphragm, and the electrolyte is a diethylene glycol dimethyl ether solution containing LiPF6.
[0039] Glass fiber membranes exhibit excellent electrolyte wettability and thermal stability. Their fine fiber diameter and high porosity, combined with good compatibility with three-dimensional carbon cloth structures, ensure the stability of Li... + Uniform transmission between the positive and negative poles.
[0040] Ether electrolytes, such as diethylene glycol dimethyl ether solutions containing LiPF6, exhibit better reduction stability on the lithium metal anode surface compared to ester electrolytes. They can form thinner, more uniform, and more ionicly conductive SEI films and have excellent interfacial compatibility with the functional groups on the modified carbon cloth surface.
[0041] The size matching between the glass fiber separator and the modified carbon cloth ensures the reliability of battery assembly and low short-circuit rate; the ether electrolyte and the oxygen- and chlorine-containing functional groups on the surface of the modified carbon cloth have good chemical compatibility, and no side reactions will occur that consume the active functional groups, thus ensuring the durability of the lithium-affinity properties of the modified carbon cloth; the battery system exhibits good electrochemical performance in a wide temperature range of -20℃ to 60℃, and has practical application value.
[0042] Based on the above-mentioned carbon cloth-based three-dimensional current collector material and its preparation method, lithium metal anode, and battery, the present invention provides the following embodiments: (1) Commercial carbon cloth was ultrasonically cleaned in ethanol / water respectively. The ultrasonic intensity was 30 kHz and the temperature was controlled at 30 ℃ during the ultrasonic process.
[0043] (2) The carbon cloth obtained in step (1) is treated in hydrochloric acid solution.
[0044] In step (1), the ethanol is anhydrous ethanol, the water is deionized water, and the washing time is 0.5 h.
[0045] In step (2), the concentration of hydrochloric acid is 5 mol / L. -1 The processing time is 5 hours.
[0046] In the comparative examples, the acid-treated carbon cloth used as a three-dimensional current collector for lithium metal anodes exhibits more stable electrochemical performance.
[0047] Electrodeposition of lithium metal onto carbon cloth three-dimensional current collector material includes the following steps: assembling a half-cell on acid-treated carbon cloth and lithium metal wafers, and performing electrodeposition on a blue electric system.
[0048] The assembly steps for the half-cell were as follows: lithium metal discs were used as the negative electrode, glass fiber as the separator, and acid-treated carbon cloth as the positive electrode, using an ether-based electrolyte. The coin cells were assembled in a glove box under an argon atmosphere. The electrodeposition process was performed on a blue electrode system. Nucleation overpotential data were obtained simultaneously. The diameter of the lithium metal discs was 10-16 mm, the glass fiber separator was Whatman GF / A, and the diameter of the acid-treated carbon cloth was 16 mm. The ether-based electrolyte was 1 M LiPF6 dissolved in diethylene glycol dimethyl ether. The coin cell model was Celgard CR2016.
[0049] The electrodeposition steps are as follows: at 0.1 mA / cm 2 The current density deposited on acid-treated carbon cloth has a deposition capacity of 3 mAh / cm³. 2 Lithium metal.
[0050] Depend on Figure 3 It can be seen that the acid-treated carbon cloth, as a three-dimensional current collector for lithium metal anodes, exhibits low overpotential and excellent rate performance.
[0051] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A method for preparing a carbon cloth-based three-dimensional current collector, characterized in that, Includes the following steps: Commercial carbon arrays were ultrasonically cleaned in a mixture of alcohol solvent and water to obtain a purified material. The purification material is immersed in an acid solution to introduce oxygen-containing functional groups and / or chlorine-containing functional groups on the surface of the carbon cloth, thereby obtaining a carbon cloth-based three-dimensional current collector material. The ultrasonic cleaning frequency is 20-60kHz, the immersion treatment is carried out at a temperature of 25-80℃, and the treatment time is 3-8 hours.
2. The method for preparing the carbon cloth-based three-dimensional current collector according to claim 1, characterized in that, The alcohol solvent is anhydrous ethanol, the water is deionized water, and the ultrasonic cleaning time is 0.5-2 h.
3. The method for preparing the carbon cloth-based three-dimensional current collector according to claim 1, characterized in that, In the mixture of alcohol solvent and water, the volume ratio of alcohol solvent to water is 1:
1.
4. The method for preparing the carbon cloth-based three-dimensional current collector according to claim 1, characterized in that, The concentration of the acid solution is 5-10 mol / L. -1 The soaking time is 2-10 h.
5. The method for preparing the carbon cloth-based three-dimensional current collector according to claim 1, characterized in that, The acid solution is nitric acid, sulfuric acid, or a mixture of nitric acid and sulfuric acid.
6. A carbon cloth-based three-dimensional current collector, characterized in that, The carbon cloth-based three-dimensional current collector is prepared by any one of claims 1 to 5, wherein the surface of the carbon cloth-based three-dimensional current collector contains oxygen-containing functional groups and / or chlorine-containing functional groups introduced by the acid treatment.
7. A lithium metal anode, characterized in that, include: The carbon cloth-based three-dimensional current collector material is the carbon cloth-based three-dimensional current collector material according to claim 6; Lithium metal is loaded onto the carbon cloth-based three-dimensional current collector material via electrochemical deposition.
8. The lithium metal anode according to claim 7, characterized in that, The lithium metal electrodeposition capacity is 1~5 mAh / cm³. -2 .
9. A battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is a lithium metal negative electrode as described in any one of claims 7 to 8.
10. The battery according to claim 9, characterized in that, The diaphragm is a glass fiber diaphragm, and the electrolyte is a diethylene glycol dimethyl ether solution containing LiPF6.